Deformation of soft particles with controlled elasticity by liquid–liquid interfacial tension. Issue 23 (31st May 2019) - Sapotta, Benedikt; Kim, Jongmin Q.; Willenbacher, Norbert; Choi, Siyoung Q.
Abstract : In this study we report the deformation of PDMS-based particles at a liquid–liquid interface under complete wetting conditions. By controlling the particle softness, we identified five deformation regimes. Abstract : Herein we report the deformation of PDMS-based particles at a liquid–liquid interface at varying degrees of softness. Direct visualization of the particle adsorption to the interface reveals at least five different modes of deformation from the complete spreading of a polymer resin droplet to a non-deforming, rigid particle.